The impact of knowledge and attitude of leprosy following a public awareness session in patients visiting dermatology OPD - Ganiger Veena; Nagesha Parvathi; Nirvanappa Vinay; Ittigi Vivekananda; Rangegowda Suresh (Our Dermatology Online, 2021)
Background: The lack of knowledge, stigma and misconception are the major barrier in leprosy control program.This study was aimed at assessing the knowledge and behavior towards the leprosy after the awareness session conducted for the patients visiting the out patient department of dermatology. Materials and Methods: Aquestionnairebasedcross sectional study was conducted on patients to evaluate knowledge and attitudes towards leprosy before and after the awareness session. Results: Total 177 subjects between age group 18 and 60 years were included. After the awareness program,knowledge about leprosy, it's cause, course, complications, treatment and attitude of the patients towards leprosy was changed positively. The difference was significant (P <0.001, McNemar test). The knowledge regarding mode of spread,side effects of treatment did not change after the awareness program. Conclusion: The awareness session had a positive impact on study subjects in terms of knowledge and attitude towards leprosy.